Development and introduction of a document disclosing AI-use: exploring self-reported student rationales for artificial intelligence use in coursework: a brief research report - Garcia Ramos, Jennifer (Frontiers in Education, 2025)
This brief research report presents exploratory findings from a study examining student-use of a mandatory artificial intelligence (AI) disclosure form in a general chemistry and citizen science honors course. Students documented every instance of AI use, describing the AI tool utilized, their purpose, the context of the assignment and their perceived outcomes. Originally created as a practical solution, the form aligns retrospectively with established frameworks in AI Literacy, Digital Ethics, Universal Design for Learning (UDL), and Metacognitive Reasoning. Qualitative analysis of responses identified major themes: verification, immediate academic aid, procrastination, and material obstacles. Findings underscore the disclosure form’s potential as a pedagogical tool, fostering transparency, ethical engagement, and self-regulation. The author proposes broader adoption of the form as a replicable strategy for instructors integrating AI in the classroom and advocates for exposing students to literacy in AI, ethics, and intellectual property.